Pelatihan Digital Markrting Sebagai Strategi Pemasaran Produk PKK di Desa Sawu Sumberejo - Darianto; Didik Puji Wahono; Ardiansyah Ahsanul H; Mesra Surya Arifien; Desi Wulandari (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Most of the activities carried out by the Sumberejo Village PKK Group have been directed to productive and marketable activities. Some of these products can be produced by the PKK group within a certain period of time. Based on the analysis of the situation, a special way or strategy is needed in marketing these products, because so far marketing is still carried out in the local scope or only limited to word of mouth. This activity aims to increase knowledge related to product marketing strategies to PKK groups through digital marketing training. The method of implementing this activity is direct training as well as practice on the online applications used, namely Facebook and Instagram. The result of this activity is that members of the PKK group can create online accounts specifically to market the products produced through Facebook and Instagram accounts.